Investigating the role of cell wall-anchored proteins during Staphylococcus aureus skin infection and as vaccine antigens - LACEY, KEENAN (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
Staphylococcus aureus has become increasingly resistant to antibiotics and community acquired methicillin resistant S. aureus (CA-MRSA) skin and soft tissue infections (SSTIs) are occurring with increasing frequency in healthy individuals. As skin is the most frequent site of S. aureus infection, a vaccine specifically targeted against SSTIs would be of great benefit. However, to date, all vaccine approaches to protect against S. aureus infection have failed, likely due to the inefficient induction of cellular immunity. It is now accepted that T cells are essential for promoting a successful immune response against S. aureus infection. However, there is a paucity of information regarding T cell antigens of S. aureus. S. aureus can express a large number of cell wall-anchored (CWA) proteins, which are covalently attached to the cell wall peptidoglycan. The virulence potential of many CWA proteins has been demonstrated in infection models, however, there is a lack of information regarding their roles during SSTIs, and whether they represent attractive T cell antigens remains to be established. This study demonstrates the ability of S. aureus CWA proteins to activate human T cells, specifically, inducing antigen-specific Th1 and Th17 responses. Importantly this study has demonstrated that clumping factor A (ClfA) has the capacity to induce robust T cell responses, and that the full length ClfA N123 protein is required for maximum Th1 and Th17 activation both in vitro and in vivo. This work also supports the use of CWA proteins as vaccine antigens, as they have the ability to induce both neutralising antibodies but more importantly, are capable of driving a much-needed cellular immune response. CWA proteins were found to be specifically important in determining abscess formation and structure, which in turn impact upon infection outcomes during subcutaneous skin infection. Most interestingly, a novel role for clumping factor B (ClfB) was discovered during SSTIs. ClfB appears to determine the abscess structure early in infection, which is dependent upon its interaction with the ligand loricrin. Consequently, a model vaccine comprising of ClfB was developed which induced humoral and cellular responses, ultimately leading to protection during subsequent S. aureus skin infection. Overall, this thesis highlights an important role for CWA proteins during SSTIs, and highlights their ability to activate cellular and humoral immune responses, capable of inducing protection against S. aureus SSTIs. Thus, identifying them as important vaccine antigens for future SSTI vaccines.
APPROVED
Keywords: Staphylococcus aureus; Vaccine; T cell; Cell wall-anchored proteins; Clumping factor A; Clumping factor B